Wagarowanie jako praktyka społeczna młodzieży elitarnych i nieelitarnych liceów poznańskich = Truancy as a social practice of Poznań elite and non-elite secondary school pupils - Cylkowska-Nowak, Mirosława (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Truancy is a phenomenon concomitant with school since its early dawn. Children and youth oppose teachers, parents and state authorities by undertaking that form of resistance. Unexplained absence is often accompanied by the infraction of the compulsory education legal rule. Most researches concerning the phenomenon of truancy show its "dark side".
Keywords: szkolnictwo polskie; szkolnictwo ponadpodstawowe; wagary; młodzież miejska; Poznań